Isolation and Characterization of Diesel – Degrading Bacteria from the Antarctica - Ali Hassan, Nor Ayshah Alia (2006)
Several isolates of bacteria with diesel-degrading capability have been isolated and characterized from Antarctica. Three strains; isolates J2(p), J7(p) and G(k) were isolated and selected for further investigations. Microbiological analysis such as gram staining and molecular phylogenetics were used to identify the bacteria. Bacterial growth optimization was studied based on carbon source, nitrogen source, pH and temperature. Biodegradation of diesel oil was monitored by quantitative gas chromatography (GC) analysis. The log phase for isolate J2(p) and G(k) were shown in between day four and day six while the log phase for isolate J7(p) was found in between day six until day eighth. Isolate J2(p), J7(p) and G(k) were identified as Pseudomonas stutzeri, Pseudomonas fluorescens and Rhodococcus sp., respectively using substrate utilization patterns (Biolog). Isolate J2(p) and G(k) showed optimum growth at 3% diesel concentration whilst isolate J7(p) was optimum at 2.5% diesel. Isolate J2(p) exhibits an optimum concentration of ammonium sulphate at 2% whilst isolate J7(p) and G(k) exhibit an optimum concentration of ammonium sulphate at 1%. The optimum pH for growth of all isolates J2(p), J7(p) and G(k) were pH 7.13, 7.15 and 7.23, respectively. All the isolates showed that 10°C was the optimum temperature for bacterial growth. The biodegradation of diesel oil by isolate J2(p) increased in efficiency from the second to the sixth day of incubation, increasing from 1.4 to 18.8% and remain constant until the eighth day. The biodegradation efficiency decreased from 18.8 to 6.3% after the eighth day. The Biodegradation efficiency (BE) of isolate J2(p) was negligible until day 2 where a linear increase in BE to 19% on the sixth day occurs. For isolate J7(p), the biodegradation efficiency was between the second and eighth day of incubation, which increasing from 0.8 to 18.7%. Then it decreased from 18.7 to 9.4% between the eighth day and tenth day of incubation. The biodegradation efficiency of isolate G(k) increase from 0.9 to 17.4% from the second to the sixth day of incubation before decreasing to day ten from 17.4 to 9.9%. Isolate J2(p) was chosen for the screening of enzyme assays. Activity was detected in isolate J2(p). The enzymes activity was distributed in cell-free extracts, soluble fraction and particulate fraction with respective activities for each fraction for n - alkane oxidizing enzyme at 0.04, 0.19 and 0.23 μmol/min-1, DCPIP-dependent dehydrogenase at 0.002, 0.006 and 0.02 μmol/min-1 and aldehyde reductase activity at 0.02, 0.09 and 0.24 μmol/min-1.